Odpowiedź :
a) 3(0,4x + 1,2) - 2(0,3x - 2,6) = 0,1x
1,2x + 3,6 - 0,6x + 5,2 = 0,1x
0,6x + 8,8 = 0,1x
0,5x = - 8,8 / :0,5
x = -17,6
b) 2,7x + 0,3 = 5(0,2x - 3,2) - (1,7 - 2,3x)
2,7x + 0,3 = x - 16 - (1,7 - 2,3x)
1,7x + 16,3 = -1,7 + 2,3x
18 = 0,6x / :0,6
x = 30
c) 0,6x + 0,2(x - 1) = 0,2(2 - x)
0,6x + 0,2x - 0,2 = 0,4 - 0,2x
0,8x - 0,2 = 0,4 - 0,2x
x - 0,2 = 0,4
x = 0,6
d) 0,7(x + 2) = 0,4(x + 1) + 0,3x + 1
0,7x + 1,4 = 0,4x + 0,4 + 0,3x + 1
0,7x + 1,4 = 0,7x + 1,4
x ∈ R
RÓWNANIE TOŻSAMOŚCIOWE
e) 0,15(2x + 4) = 2(1,3 + 0,3x) - 0,6
0,3x + 0,6 = 2,6 + 0,6x -0,6
0,3x + 0,6 = 2 + 0,6x
0,6 = 2 + 0,3x
-1,4 = 0,3x / :0,3
x = 4,(6)
f) 1,4x - 3(0,7x - 1,3) = 0,5(4x - 3)
1,4x - 2,1x + 3,9 = 2x - 1,5
-0,7x + 3,9 = 2x - 1,5
3,9 = 2,7x -1,5
5,4 = 2,7x / :2,7
x = 2
g) 0,2(x + 1) + 0,5(0,3x - 1) = 5(0,08 + 0,07x)
0,2x + 0,2 + 0,15x - 0,5 = 0,4 + 0,35x
0,35x - 0,3 = 0,4 + 0,35x
-0,3 = 0,4
RÓWNANIE SPRZECZNE
h) 4(0,15x - 0,1) - 0,8(3x - 2) = 0,6(2 - 0,3x)
0,6x - 0,4 - 2,4x + 1,6 = 1,2 - 0,18x
-1,8x + 1,2 = 1,2 - 0,18x
-1,8 x = -0,18x
-1,62x = 0
x = 0